Barriers to cervical cancer prevention in a safety net clinic: gaps in HPV vaccine provider recommendation and series completion among Ob/Gyn patients - Finch, Lindsey A.; Levy, Morgan S.; Thiele, Amanda; Jeudin, Patricia; Huang, Marilyn (Frontiers in Oncology, 2024)
Objective The primary objective of this study was to evaluate patients’ knowledge regarding HPV vaccination and vaccine uptake in a diverse patient population. The secondary objective was to evaluate factors influencing the decision to vaccinate, potential barriers to vaccination, and to assess whether HPV vaccines were offered to or discussed with eligible patients in a safety net Obstetrics and Gynecology (Ob/Gyn) clinic. Methods A 28-item survey was developed using Likert scale survey questions to assess patient agreement with statements regarding HPV and the vaccine. The surveys were administered to patients in the Ob/Gyn outpatient clinics from May 2021 through September 2022. Additionally, pharmacy data were reviewed and chart review was performed as a quality improvement initiative to assess the impact of expanded HPV vaccine eligibility to patients with private insurance on vaccine uptake. Descriptive statistics were performed. Results 304 patients completed surveys from May 2021 through September 2022. The median age of respondents was 32 (range 18-80). 16 (5%) were Non-Hispanic White, 124 (41%) were Hispanic White, 58 (19%) were Non-Hispanic Black, 6 (2%) were Hispanic Black, 29 (9.5%) were Haitian, 44 (14%) were Hispanic Other, 7 (2%) were Non-Hispanic Other, 20 (6.6%) did not respond. 45 (14%) patients were uninsured. Many patients (62%) reported that a physician had never discussed HPV vaccination with them. Seventy nine percent of patients reported they had never received the HPV vaccine, and 69% of patients reported that lack of a medical provider recommendation was a major barrier. Among patients to whom HPV vaccination had been recommended, 57% reported that the vaccine was not available the same day in clinic. Conclusion Our study demonstrated that many patients never had a provider discuss HPV vaccination with them and never received the HPV vaccine. Additionally, amongst those who did initiate HPV vaccination, completion of the series remains a key barrier. Ensuring that providers discuss HPV vaccination and that patients receive HPV vaccines, along with expanding access to and convenience of HPV vaccination are critical aspects of preventing cervical cancer.